Integrated water resources management for disaster prevention in the face of climate change - YANG, Kyoung Jun (KDI School, 2024)
According to the Intergovernmental Panel on Climate Change (IPCC), the temperature of the entire Earth's surface has risen faster since 1970 than any other period (50 years) in the past 2,000 years, and in many respects, the current climate system is on a scale that has not been experienced for thousands of years. Recently, climate change and dams have a strong correlation. This is because it is the most efficient facility to prepare for droughts and floods due to climate change, and at the same time, downstream areas can suffer great damage in the event of dam problems and extreme discharge due to climate change. Recently, climate change and dams have a strong correlation. This is because it is the most efficient facility to prepare for droughts and floods due to climate change, and at the same time, downstream areas can suffer great damage in the event of dam problems and extreme discharge due to climate change. Recent climate change is causing many difficulties in dam water management measures. In the case of Chungju Dam, there is a significant difference between the climate at the time of design in 1978 and the current climate change. It appears that there is a limit to the dam's capacity due to the changed climate. If extreme rainfall may occur in the area and floods are difficult to accommodate at the Chungju Dam, the dam will overflow, which is highly likely to lead to dam collapse and secondary damage. The problem of the Chungju Dam is not just a facility problem, but a serious matter that can cause massive flood damage throughout the metropolitan area and even lead to a national disaster, such as water supply and power production being stopped if the freshwater function is lost. It is important to prepare proactive measures.
Thesis(Master) -- KDI School: Master of Public Management, 2024
Keywords: Water-supply--Korea (South)